Comparison of Intraocular Cytokine Levels of Choroidal Neovascularization Secondary to Different Retinopathies - Liu, Chenyi; Zhang, Shian; Deng, Xinyi; Chen, Yijing; Shen, Lijun; Hu, Liang; Mao, Jianbo (Frontiers in Medicine, 2021)
Abstract Purpose: To investigate and compare the aqueous concentrations of vascular endothelial growth factor (VEGF) and other inflammatory cytokines in various choroidal neovascularization (CNV) diseases and types. Methods: This observational study included 127 naive eyes with CNV and 43 control eyes with cataracts. Aqueous humor (AH) samples were obtained prior to intravitreal anti-VEGF injection or cataract surgery. Multiple inflammatory cytokines, including VEGF, interleukin (IL) 6, IL-8, IL-10, interferon-inducible protein 10 (IP-10), and monocyte chemotactic protein 1 (MCP-1) levels, were measured using a multiplex bead assay. The angiogenesis index was defined as the ratio of IP-10 to MCP-1. In addition, the relationship among AH cytokine levels, central macular thickness (CMT), and CNV size on optical coherence tomography angiography (OCTA) was evaluated. Results: Except in the myopic CNV group (P = 0.452), the AH concentration of VEGF was significantly higher in all other CNV groups than in the control group (P<0.05 for all comparisons). IL-8, IL-10, IP-10, and MCP-1 levels (P< 0.05 for all groups) were significantly higher in all CNV diseases except those with neovascular central serous chorioretinopathy. The angiogenesis index was significantly higher in all CNV diseases (P< 0.05 for all comparisons). The VEGF level may be associated with the size of the CNV on OCTA (p=0.043). Conclusions: The level of intraocular inflammatory cytokines varied among different CNV diseases and CNV types. Therefore, the angiogenesis index may be a more sensitive indicator of angiogenesis.